PENGARUH PEMBERIAN JUS JERUK TERHADAP MUAL MUNTAH PADA IBU HAMIL TRIMESTER 1 - Septa Dwi Insani; Naimah Nasution (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2026)
Nausea and vomiting are frequent complaints during the first trimester, affecting around 70–80% of expectant mothers. These symptoms may lead to a decrease in appetite, dehydration, and potentially hinder fetal development if not addressed appropriately. One natural, non-drug-based option to help alleviate these issues is orange juice consumption. This research aimed to explore the impact of orange juice intake on nausea and vomiting in first-trimester pregnant women at the Fatimah Ali II Clinic, Deli Tua, in 2025. A quasi-experimental method with a one-group pretest-posttest design was used, involving 15 participants. Data were gathered using observation sheets and analyzed with the Wilcoxon signed-rank test. Results showed a statistically significant reduction in nausea and vomiting frequency after consuming orange juice, with a p-value of 0.002 (p < 0.05). These findings indicate that orange juice can effectively reduce nausea and vomiting during early pregnancy. Its rich content of vitamin C, folate, and antioxidants makes it a safe, natural, and cost-effective solution for managing morning sickness. This study aims to support the use of non-pharmacological approaches in addressing common pregnancy discomforts